Литологические особенности и органическое вещество осадочных отложений юго-восточной части моря Лаптевых (мыс Муостах) - Перевертайло Татьяна Геннадьевна; Кажумуханова Малика Зейнеллаевна; Недоливко Наталья Михайловна; Гринько Андрей Алексеевич; Шахова Наталья Евгеньевна; Дударев Олег Викторович; Гершелис Елена Владимировна; Мазуров Алексей Карпович; Семилетов Игорь Петрович; Perevertaylo (Perevertailo), Tatyana Gennadievna; Kazhumukhanova, Malika Zeinellaevna; Nedolivko, Nataliya Mikhailovna; et al. (Томский политехнический университет, 2019)
Актуальность исследования продиктована необходимостью изучения современных изменений климата, которые рассматриваются как последствия парникового эффекта, обусловленного ростом содержания в атмосфере основных парниковых газов -двуокиси углерода и метана. Для изучения этой проблемы и построения модели климата необходимо проведение комплексных исследований в системе суша-шельф-атмосфера на Арктическом шельфе, включая оценку потенциала морей Восточной Арктики в контексте особенностей литологического состава и трансформации органического вещества в углеводороды в процессе диагенетических и катагенетических преобразований. Цель: изучение литологического и минералогического составов, изменчивости содержания органического вещества (Сорг), молекулярного и изотопного состава углерода (δ13C) в отложениях ледового комплекса побережья моря Лаптевых (мыс Муастах). Объект: пробы современных донных осадков, отобранных в ходе проведения экспедиционных работ 2015 г. в юго-восточной части моря Лаптевых. Методика исследования донных отложений включает в себя пробоподготовку, лабораторно-аналитические исследования (хроматомасс-спектрометрия, пиролиз, изотопия, рентгенофазовый анализ, методы обработки и интерпретации результатов). Результаты. Изучен минералогический состав глинистой фракции, установлена зональность распределения глинистых минералов. Выявлены особенности состава органического вещества на молекулярном и изотопном уровнях. Получены первые результаты по потенциалу генерации углеводородов из органического вещества осадков ледового комплекса, которые доминируют в мелководной части Восточно-Сибирского шельфа. Результаты исследований, полученные по данным пиролиза и хроматомассспектрометрии, имеют высокую степень корреляции и отражают комплекс биохимических процессов, сопровождающих превращение органического вещества на различных стадиях литогенеза. Кроме того, приведены первые оценки потенциала генерации легких углеводородов из Сорг исследуемых осадков.

The present study seeks to improve current understanding of modern climate changes, which are considered as the consequences of the greenhouse effect caused by increasing content of the main greenhouse gases - carbon dioxide and methane. Complex studies in the land-shelf-atmosphere system across the Arctic shelf, including biogeochemical and lithological analyses of sediments across Eastern Arctic seas, are needed. The research aims to study both lithological and mineralogical sediment compositions, variability of the organic matter content (Corg), molecular and isotopic composition of carbon (δ13C) contained in the ice complex deposits (ICD) along the Laptev Sea coast (Cape Muostakh). Samples of modern bottom sediments obtained during the expedition of 2015 in the south-eastern part of the Laptev Sea were investigated. Methods used in the present study include GC:MS analysis, pyrolysis, isotope analysis, X:ray phase analysis followed by further numerical processing and interpretation. Results. The mineralogical composition of the clay fraction has been studied, and the distribution of clay minerals has been established. The features of molecular and isotopic Corg composition are revealed. Initial results on the hydrocarbon source of ICD:Corg, which dominates in the shallow part of the East Siberian Arctic shelf, are obtained. Pyrolysis and GC:MS data are highly correlated reflecting complex biogeochemical processes occurring during the Corg transformation at the various stages of lithogenesis. In addition, the study provides preliminary estimates of the light hydrocarbons generation potential for the Corg contained in the sediments. The aim of the work is to study the chemical composition of biological water of individual organs and tissues, on the example of domestic pigs, to obtain background characteristics for biogeochemical monitoring. The methods. Organs and tissues of seven-month domestic pig was sampled in Uspenka village, Pavlodar region (Kazakhstan) just after the slaughter and packed in plastics packages. Biological water was exudated by vacuum sublimation method upon the application of heat. The exudate was analyzed in certificated scientific-education center «Water» at Tomsk Polytechnic University by the method of inductively coupled plasma mass spectrometry according to the certified HCAM 480X method with NeXION 300D spectrometer. Result. The authors have studied the composition and characteristics of distribution of 70 chemical elements in biological water, separated by vacuum sublimation from the organs and tissues of the domestic pig, selected on the territory of the conditionally environmentally friendly village Uspenka, Pavlodar region. The interrelation between the elemental composition of the biological fluid and the physiological functions of the organs of the animals studied as well as the composition of the habitat was revealed.
Lithological features and organic matter of sediments in the south-eastern Laptev sea (Muostakh Cape)
Keywords: органические вещества; донные осадки; изотопный анализ; хроматомасс-спектрометрия; минералогический состав; море Лаптевых; мыс Муостах; organic matter; bottom sediments; isotope analysis; GC-MS; mineralogical composition; Laptev Sea; Cape Muostakh; background monitoring